An upriver Passamaquoddy - Sockabasin, Allen J. (Gardiner, Me. : Tilbury House, 2007)
Drawing on his memories and an oral tradition, Allen Sockabasin returns to his Passamaquoddy village of Mud-doc -mig-goog, or Peter Dana Point, near Princeton, Maine.
Our people -- Our language -- Our place -- Growing up Passamaquoddy -- The traditional ways : hunting, mealtimes, our wakes, music and dance, artists and craftsmen -- Memorable individuals -- "Progress" -- The Maine Indian land claims -- The future.
Includes bibliographical references (p. 158).
Maine author.
Keywords: Sockabasin, Allen J; Passamaquoddy Indians -- Maine -- Peter Dana Point -- Biography; Passamaquoddy Indians -- Maine -- Peter Dana Point -- Social life and customs; Passamaquoddy Indians -- Maine -- Peter Dana Point -- Government relations; Peter Dana Point (Me.) -- Social life and customs; Peter Dana Point (Me.) -- Ethnic relations; Peter Dana Point (Me.) -- Race relations